Mechanisms of flower coloring and eco-evolutionary implications of massive blooming events in the Atacama Desert - Martínez-Harms, Jaime; Guerrero, Pablo C.; Martínez-Harms, María José; Poblete, Nicolás; González, Katalina; Stavenga, Doekele G.; Vorobyev, Misha (Frontiers in Ecology and Evolution, 2022)
The Atacama Desert, the driest place on earth, holds a rich biodiversity that becomes most appreciable in years when unusual rainfall accumulation triggers a phenomenon of explosive development of ephemeral herbaceous and woody desert species known as ‘desierto florido’ or ‘blooming desert’. Despite the scientific importance of this unique phenomenon only few studies have addressed the mechanisms of flower phenotypic divergence under the fluctuating environment provided by this recurrent event. We investigated the mechanisms of floral color diversity in Cistanthe longiscapa (Montiaceae), a dominant species across the ephemeral blooming landscape of Atacama Desert. Our analyses show that the variation in colors of C. longiscapa flowers result from petals containing betalain pigments with different absorption spectra. The different pigment composition of petals causes flower color differences in the visible and UV range of the spectrum. Through color vision models we show that C. longiscapa flowers are highly polymorphic in their color appearance for insect pollinators. Our results highlight the variable nature in flower color of C. longiscapa varieties blooming simultaneously in a geographical restricted area. Given the importance of color in attracting floral visitors, the observed color variability could contribute to increased cross pollination in extreme desert conditions, while accounting for complex and fluctuating histories of plant-pollinator interactions.